Phenotypic associations of genetic susceptibility loci in systemic lupus erythematosus (2011)
Objective: Systemic lupus erythematosus is a clinically heterogeneous autoimmune disease. A number of genetic loci that increase lupus susceptibility have been established. This study examines if these genetic loci also contribute to the clinical heterogeneity in lupus. Materials and methods: 4001 European-derived, 547 Hispanic, 1590 African-American and 1191 Asian lupus patients were genotyped for 16 confirmed lupus susceptibility loci. Ancestry informative markers were genotyped to calculate and adjust for admixture. The association between the risk allele in each locus was determined and compared in patients with and without the various clinical manifestations included in the ACR criteria. Results: Renal disorder was significantly correlated with the lupus risk allele in ITGAM (p=5.0 × 10-6, OR 1.25, 95% CI 1.12 to 1.35) and in TNFSF4 (p=0.0013, OR 1.14, 95% CI 1.07 to 1.25). Other significant findings include the association between risk alleles in FCGR2A and malar rash (p=0.0031, OR 1.11, 95% CI 1.17 to 1.33), ITGAM and discoid rash (p=0.0020, OR 1.20, 95% CI 1.06 to 1.33), STAT4 and protection from oral ulcers (p=0.0027, OR 0.89, 95% CI 0.83 to 0.96) and IL21 and haematological disorder (p=0.0027, OR 1.13, 95% CI 1.04 to 1.22). All these associations are significant with a false discovery rate of and lt;0.05 and pass the significance threshold using Bonferroni correction for multiple testing. Conclusion: Significant associations were found between lupus clinical manifestations and the FCGR2A, ITGAM, STAT4, TNSF4 and IL21 genes. The findings suggest that genetic profiling might be a useful tool to predict disease manifestations in lupus patients in the future.